Pengaruh Ekspor dan Impor Terhadap Pertumbuhan Ekonomi Di Indonesia Pada Tahun 2018-2022 - Agustina Mogi; Lativa Lativa (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2023)
This study uses a quantitative approach to analyze the relationship between the balance of payments (exports and imports) as the dependent variable and economic growth as the independent variable in Indonesia. The data used in this research is time series data from 2018 to 2022 obtained from the Central Bureau of Statistics (BPS). The results of the study show that in the long term, the amount of exports and imports has a significant effect on economic growth. The increase in exports indicates an increase in demand from other countries, which encourages an increase in domestic production. However, an increase in imports can reduce domestic productivity and potentially reduce economic growth. In the short term, increased exports and imports also have a positive and significant impact on economic growth. Increased exports can increase domestic production and contribute to economic growth in Indonesia. Therefore, an increase in domestic production is needed to drive the economy. This study uses the Error Correction Model (ECM) to analyze the relationship between these variables. The test results show that the variables are cointegrated with each other and the error correction is valid. Thus, it can be concluded that exports and imports affect economic growth both in the long and short term. This conclusion has important implications for formulating economic policy in Indonesia. The government needs to pay attention to international trade policies and make efforts to increase exports and control imports to encourage sustainable economic growth.